THE GRAMMATICAL MEANING OF DESCRIPTIVE ADJECTIVES, DERIVATIONAL VERBS, AND EXPLETIVES IN ENGLISH NEWS TEXTS: A SYSTEMIC FUNCTIONAL LINGUISTICS - Shenna Swantika Sari; Daffa Nabil Ahmad; Cha Limah (Universitas Negeri Surabaya, 2026)
Using the framework of Systemic Functional Linguistics (SFL), this study examines the grammatical meaning of descriptive adjectives, derivational verbs, and expletive constructions in English news stories. The study is to investigate how these lexical-grammatical elements support the development of meaning in news discourse, namely in the representation of events, participants, and information organization. Three English news stories from CNN Business, BBC News, and The Jakarta Post were used to gather data using a qualitative descriptive method. Miles, Huberman, and Saldaña's interactive model and Halliday and Matthiessen's SFL framework were used to examine the data. The results demonstrate that descriptive adjectives are the most prevalent feature and primarily serve in ideational and interpersonal meanings by characterizing and assessing people and economic occurrences. While expletive constructions contribute to textual meaning by structuring information and enhancing discourse coherence, derivative verbs contribute to ideational meaning by using morphological derivation to depict actions and processes. Even though they are uncommon, expletives are nonetheless useful for organizing news texts. The study comes to the conclusion that many lexical-grammatical resources interact to build grammatical meaning in news discourse rather than separate linguistic elements, with each feature contributing to textual, interpersonal, and ideational metafunctions in SFL.